Vibrotactile sensitivity of patients with HIV‐related sensory neuropathy: An exploratory study. Issue 1 (18th December 2018) - Karpul, David; McIntyre, Sarah; van Schaik, André; Breen, Paul P.; Heckmann, Jeannine M.
Abstract: Background: HIV‐associated distal polyneuropathy (HIV‐PN) affects large and small sensory nerve fibers and can cause tactile insensitivity. This exploratory study forms part of an effort to apply subsensory electrical nerve stimulation (SENS) to improve tactile sensitivity of patients with HIV‐PN. This work presented an opportunity to use a robust protocol to quantitatively describe the vibrotactile sensitivity of individuals with HIV‐PN on effective antiretroviral therapy (ART) and correlate these findings with commonly used clinical vibration testing and scoring grades. Methods: The vibration perception thresholds (VPTs) of 20 patients with HIV‐PN at three vibration frequencies (25, 50, and 128 Hz) were measured. We compare the vibration perception threshold (VPT) outcomes to an age‐ and gender‐matched control cohort. We further correlated VPT findings with 128 Hz tuning fork (TF) assessments performed on the HIV‐PN participants, accrued as part of a larger study. HIV‐PN was defined as having at least one distal symmetrical neuropathic sign, although 18 of 20 had at least two neuropathic signs. Conclusions: HIV‐PN participants were found to have lower VPT sensitivity than controls for all three vibration frequencies, and VPT was more sensitive at higher vibration frequencies for both HIV‐PN and controls. VPT sensitivity was reduced with older age. Years on ART was correlated with VPT‐25 Hz but not with VPT in general. Notably, VPT sensitivity did not correlate with the clinically used 128 Hz TF severity grades. Outcomes of tests for interaction with vibration frequency suggest that HIV‐PN pathology does not affect all mechanoreceptors similarly. Abstract : HIV‐associated distal polyneuropathy (HIV‐PN) affects large and small sensory nerve fibers and can cause tactile insensitivity. We report a detailed description of the vibrotactile sensitivity of individuals with HIV‐PN and compare the commonly used clinical vibration testing and scoring grades with a more robust double‐blinded quantitative vibration perception thresholds (VPTs) protocol. The results indicate that patients with HIV‐PN have reduced vibration sensitivity at all tested vibration frequencies and that the pathology may not affect all mechanoreceptors similarly.